Pengembangan Biskuit Canavalia Kaya Protein Berbahan Dasar Tepung Kacang Koro Pedang terhadap Daya Terima dan Kandungan Zat Gizi sebagai Makanan Tambahan Ibu Hamil untuk Pencegahan Stunting: Development of Protein-Rich Canavalia Biscuit from Koro Sword Bean Base on Acceptance and Nutritional Content as Additional Food for Pregnant Women for Stunting Prevention - Septiani, Baiq Dewi Sukma; Ardiansyah, Lalu Dwi Satria (Universitas Airlangga, 2024)
Background: One of the efforts to overcome the problem of stunting in toddlers, especially in Central Lombok Regency, is to improve the nutritional status of mothers during pregnancy, especially mothers with chronic energy deficiency (KEK). The PMT program for pregnant women has been regulated in Regulation of the Ministry of Health Number 51 of 2016, where pregnant women with KEK conditions are given a nutrition improvement program that has been set by the government, namely by providing additional food (PMT) in the form of biscuits. Objectives: Developing additional food products for pregnant women in the form of biscuits using local food ingredients sourced from the koro sword bean. Methods: The research design used a randomized block design (RBD) with 3 treatments (K=3), 1 experimental unit and 3 repetitions, so the total number of trials was 3×1×3=9. Koro bean flour was also added to Canavalia Biscuit products with different doses, and then the results were analyzed, including tests of acceptability and nutrient content including energy, protein, fat, carbohydrates and calcium. Results: The results showed that adding 50 g of jack bean flour increased the acceptability of respondents in terms of color, aroma, texture, and taste. The addition of 50 g koro bean flour to Canavalia biscuit products increases the nutritional content, including energy, protein, fat, carbohydrates as well as calcium. The best nutritional content of